Impact and static behavior of strain-hardening cementitious composites–strengthened reinforced concrete slabs. Issue 8 (June 2020) - Mahmoud, Mohamed H; Afefy, Hamdy M; Baraghith, Ahmed T; Elnagar, Amira B
Impact loading could impair the entire structure or a part of it, thus making the human life at stake. In this study, to improve the impact resistance of reinforced concrete slabs under drop-weight loading, a thin layer of strain-hardening cementitious composites was added at either tension or compression side of the slab. The main parameter of this study was the three contact surface conditions, namely grinding, grinding plus steel dowels, and grinding plus epoxy adhesive, between the substrate slab and the strain-hardening cementitious composites layer. Therefore, 63 reinforced concrete slabs were prepared and tested under the effect of drop-weight falling from three different heights: 1, 1.5, and 2 m. In addition, for comparison purposes, additional seven slabs were tested under central incremental static loading until failure is presented. It was found that the strain-hardening cementitious composites–strengthening layer enhanced the impact and static response of the strengthened slabs when added at either tension or compression side. Besides, to achieve the outermost impact resistance showing ductile performance, it is better to provide a thin layer of the strain-hardening cementitious composites at the tension side of the slab connected to the substrate slab by epoxy resin applied on pre-prepared grinded surface.